The Philippine republic - Fernandez, Leandro Heriberto 1889-1948 (New York Columbia University Press, 2019)
Studies the Philippine revolution, meaning the armed conflict which began as a revolt against Spain and ended as an act of resistance to the United States. Looks at the government and the political ideology of the movement.
Includes bibliographical references and index.
Keywords: Philippines -- Politics and government -- 1898-.; Philippines -- History -- Revolution, 1896-1898.; Philippines -- History -- Revolution, 1899-1901.